Improving the texture of sardine surimi using duck feet gelatin - Nik Aisyah, Nik Muhammad; Haslaniza, Hashim; Nurul, Huda (2017)
Sardine surimi is classified as a low grade surimi due to its relatively poor texture quality. The objective of this study was to improve the texture quality of sardine surimi by adding duck feet gelatin. Duck feet gelatin were treated using four treatments (hydrochloric acid (SHCl), acetic acid (SAa), lactic acid (SLa), or citric acid (SCa)) before added to surimi which was prepared using sardine fish to study the effects of the additives on the quality properties (folding, gel strength, texture profile, expressible moisture (EM) content, and colour) of surimi gels. All sardine surimi samples containing gelatin showed improved texture quality compared to samples without gelatin. The folding test score increased from 1 to 4, the hardness value increased from 1103.69 g to 2579.86 g for SHCl, 5897.08g for SAa, 2713.48 g for SLa, and 6532.18 g for SCa. Gel strength improved from 1857.43 g.mm to 6655.57 g.mm, 6680.52 g.mm, 6928.21 g.mm, and 7290.00 g.mm for SHCl, SAa, SLa, and SCa, respectively. The addition of gelatin also increased the whiteness and decreased the EM of surimi gels. These findings show that duck feet gelatin has great potential for use as a protein additive for the improvement of the texture quality of sardine surimi.